Zoonotic potential of ESBL-producing coliforms in pastorally managed ruminants with subclinical mastitis in Plateau State, Nigeria - Anueyiagu, Kenneth Nnamdi; Agusi, Ebere Roseann; Kabantiyok, Dennis; Ayanbimpe, Grace Mebi; Ikeh, Eugene Ifeanyichukwu (Frontiers in Antibiotics, 2025)
BackgroundEnvironmental coliform bacteria are frequently the cause of subclinical mastitis (SCM), a serious health issue in the dairy industry. Extended-spectrum β-lactamase (ESBL)-producing coliforms in livestock are a serious public health concern, particularly in environments where people and animals coexist. With an emphasis on their zoonotic and One Health implications, this study sought to evaluate the incidence of SCM and the occurrence of ESBL-producing coliforms in ruminants in Plateau State, Nigeria.MethodsThe California Mastitis Test (CMT) was used to screen 287 milk samples that were taken from cows, ewes, and does. Standard microbiological methods were used to identify the bacterial isolates from CMT-positive samples. The presence of resistance genes (blaTEM and blaCTX-M) was ascertained by PCR, and ESBL production was confirmed phenotypically. Phylogenetic analysis showed genetic diversity and possible horizontal gene transfer among isolates.ResultsOut of 287 milk samples, 79 (27.5%) had subclinical mastitis through the CMT, with a higher prevalence recorded in does 18(22.8%) while ewes and cows recorded 23(29.1%), and 38(48.1%) respectively. Of the 79 CMT-positive samples, the following isolates were identified: Citrobacter freundii (6.3%), Klebsiella pneumoniae (21.6%), K. oxytoca (2.5%), K. aerogenes (6.3%), and E. coli, being the most prevalent in cows (71%). Through PCR, 46 isolates expressed two important ESBL genes, blaTEM and blaCTX-M.ConclusionA possible zoonotic reservoir for antibiotic resistance in Nigeria is highlighted by the increased frequency of ESBL-producing coliforms in ruminants with SCM. These results highlight the necessity of implementing integrated One Health initiatives, such as public education, surveillance, and antimicrobial stewardship, in order to reduce the risk of resistant pathogen transmission from animals to people.